Pengaruh Mode Shape Frekuensi Alami terhadap Estimasi Gaya Tarik Batang Baja dengan Metode Vibrasi - Guntur Nugroho (Semesta Teknika, 2018)
The vibration method has been widely applied to estimate the force on cable structures as well as beams. This method utilizes the natural frequency of structural elements in estimating tensile as well as compressive forces. On the cable element, a different natural frequency will appear according to the shape number. This study raises the suitability of force estimation by using the natural frequency of the first second and third modes. The steel specimen have cross section of width, thickness and length of 6 mm, 40 mm and 2000 mm respectively. The results of natural frequency, calculated by using analytic formulas (string, beam-string and stokey) has been compared with the natural frequency resulted by numerical modeling. The difference of  natural frequency of specimen calculated by using analytic formulas (strings, beam-strings, stokey), compared with the result of numerical modeling  has the smallest value in the first mode which is 3.75% at 5,000N load and 0.61% at 50,000N load.